2020
DOI: 10.21037/atm.2020.01.14
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl endopeptidase gene disruption attenuates high fat diet-induced nonalcoholic fatty liver disease in mice by improving hepatic steatosis and inflammation

Abstract: Background: Prolyl endopeptidase (PREP) is a serine endopeptidase that regulates inflammatory responses. PREP inhibitors can reduce hepatocyte lipid accumulation and may participate in the progression of nonalcoholic fatty liver disease (NAFLD). We investigated whether disruption of PREP regulates hepatic steatosis and inflammation in mice with NAFLD.Methods: Wild-type and PREP gene disrupted mice were randomly divided into low-fat diet wild-type (LFD-WT), high-fat diet wild-type (HFD-WT), low-fat diet PREP di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…Interestingly, factors associated with proinflammation and its related signaling molecules showed dynamic changes in HFD-PREP gt mice upon hepatic inflammation progression. Our previous works demonstrated that PREP could potentially affect the progression of hepatic inflammation, possibly by regulating chemotactic factors (such as PGP and MMPs) ( Jiang et al, 2020 ), and in this study, we found this effect was more important and evident in the later and more severe stage of NAFLD. This observation may be partially explained by the fact that NASH is considered a potentially progressive disorder, as liver inflammation may prompt collagen matrix synthesis and deposition ( Suzuki and Diehl, 2017 ), which PREP and MMP9 hydrolyze to produce PGP (chemotaxis of neutrophils) ( Weathington et al, 2006 ; Gaggar et al, 2008 ).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Interestingly, factors associated with proinflammation and its related signaling molecules showed dynamic changes in HFD-PREP gt mice upon hepatic inflammation progression. Our previous works demonstrated that PREP could potentially affect the progression of hepatic inflammation, possibly by regulating chemotactic factors (such as PGP and MMPs) ( Jiang et al, 2020 ), and in this study, we found this effect was more important and evident in the later and more severe stage of NAFLD. This observation may be partially explained by the fact that NASH is considered a potentially progressive disorder, as liver inflammation may prompt collagen matrix synthesis and deposition ( Suzuki and Diehl, 2017 ), which PREP and MMP9 hydrolyze to produce PGP (chemotaxis of neutrophils) ( Weathington et al, 2006 ; Gaggar et al, 2008 ).…”
Section: Discussionsupporting
confidence: 71%
“…We only detected butyrate levels in the colon of 16 weeks mice; however, a previous study reported that sodium butyrate could delay the onset of early signs of NAFLD in mice ( Jin et al, 2016 ). Our previous studies also indicated that PREP is closely related to energy metabolism and the downstream lipid metabolism targets of AMPK ( Jiang et al, 2020 ). The functional consequences of this taxa shift and our previous work provide clues about how PREP inhibition may regulate flora homeostasis, trigger the AMPK signaling pathway, and improve liver lipid metabolism.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations